Efeito da inclusão de levedura na ração de tilápias na fase larval sob os parâmetros microbiológicos, bioquímicos, físico-químico e sensorial da qualidade do filé - Costa, Patrícia Braun (2012)
This work aimed to study the different effects of supplemental yeast (Saccharomyces cerevisiae) during sex reversal in Nile tilapia (Oreochromis niloticus) represented by hybrid GIFT on microbiological parameters, biochemical, physicochemical and sensory quality during storage and sensory analysis of fresh fillets. The experiment was conducted at the premises of UPD Pirassununga, APTA Pole Middle East tilapia larvae with two days of age were placed in aquariums 40litros according to the treatments, and were fed with 60mg of the hormone 17 α metil-testosterona/kg ration for 30 days for sex reversal. Treatment with fish larvae that received the supplementation of yeast had the same diet with hormone plus the addition of 0, 1, 2, 3 and 4% yeast fully dried and milled then constituting T1, T2, T3, T4 and T5 respectively. At the end of 08 months, the fish were slaughtered. The performance was calculated. For statistical analyzes of the results we used the GLM procedure of SAS (Statistical Analysis System, 1996). To verify the significance between treatment means was used Tukey test at 5 and 1% probability. The results showed that supplementation of Saccharomyces cerevisiae in the diet of Nile tilapia shows that treatment with 1% yeast inclusion was better than the other treatments in the mean values of lipids and the lipids and triglycerides increased can not necessarily have an effect of diet, but may be a genetic trait hybrid Gift, requiring further studies to confirm this, that in addition to the sensory evaluation treatment with 2% addition of yeast showed better consumer acceptance, and purchase by panelists, and there was significant differences between treatments regarding the attributes of color, odor, taste and texture and microbiological analyzes showed no differences between treatments and storage times.